Targeting Akt/PKB in pediatric tumors: A review from preclinical to clinical trials - Bruno Toson; Isadora S. Fortes; Rafael Roesler; Saulo F. Andrade (Elsevier, 2022)
The serine/threonine kinase Akt is a major player in the phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling pathway, and its modulation impacts multiple cellular processes such as growth, proliferation, and survival. Several abnormalities in this pathway have been documented over the years, and these alterations were shown to have great implications in tumorigenesis and resistance to chemotherapy. Thus, multiple Akt inhibitors have been developed and tested in adult tumors, and some of them are currently undergoing phase I, II, and III clinical trials for distinct cancers that arise during adulthood. Despite that, the impact of these inhibitors is still not fully understood in pediatric tumors, and Akt-specific targeting seems to be a promising approach to treat children affected by cancers. This review summarizes recent available evidence of Akt inhibitors in pediatric cancers, from both preclinical and clinical studies. In short, we demonstrate the impact that Akt inhibition provides in tumorigenesis, and we suggest targeting the PI3K/Akt/mTOR signaling pathway, alone or in combination with other inhibitors, is a feasible tool to achieve better outcomes in pediatric tumors.